Development of a Thyme Essential Oil Formulation and Its Effect on Monilinia fructigena (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Antifungal activity of thyme essential oil against Monilinia fructigena and development of an effective and stable oil formulation for agricultural use were studied in this paper. Bioactivity of the oil itself and its developed formulation, an emulsifiable concentrate (EC), was tested in vitro and in vivo. In vitro experiments, using a slightly modified agar overlay technique, showed that the initially emulsified thyme essential oil, as well as the developed formulation, significantly inhibited mycelial growth of M. fructigena in vitro. Experiments in vivo, performed on inoculated apple fruits, revealed that the formulation successfully decreased oil evaporation from the treated area and provided a significant level of M. fructigena suppression, 64.7-72.1% compared to the control. To our knowledge, an EC formulation of thyme essential oil for agricultural uses had never been developed before. The presented results are initial findings and evaluation of product activity should be continued in the field to determine its efficacy and activity spectrum, and to estimate the economic aspect of its use.
Keywords: Thyme; Formulations; Essential oils